Avaliação do potencial antinociceptivo de 5- trialometil- 4,5-diidro-1h- pirazol metil ésteres inéditos em camundongos - Milano, Julie Maria (2008)
Pain is a common symptom in clinical practice and many advances have been observed in order to obtain more effective analgesic molecules with fewer side effects. The present study evaluated the antinociceptive potential of four novel pyrazoles: 3-methyl-5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazole methyl ester (MPF3), 4-methyl-5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazole methyl ester (MPF4), 3-methyl-5-trichloromethyl-5-hydroxy-4,5-dihydro-1H-pyrazole methyl ester (MPCl3), and 4-methyl-5-trichloromethyl-5-hydroxy-4,5-dihydro-1H-pyrazole methyl ester (MPCl4). The systemic administration of the compounds was effective for the inhibition of the nociception in chemical (formalin test, 0.03 -1.0 mmol/kg, i.p.) and thermal (hot-plate test, 0.1-1.0 mmol/kg, i.p.) models of pain. In addition, MPF4 also produced antinociception in models of inflammatory pain induced by Complete Freund s Adjuvant (CFA) or by incision procedure in paw of mice. The antinociceptive effect of MPF4 (1.0 mmol/kg, i.p.) was not reversed by yohimbine (0.15 mg/kg, i.p.) or p-chlorophenylalanine ethyl ester (PCPA; 300 mg/kg, i.p.), but by naloxone (2.0 mg/kg, i.p.), in both thermal and chemical nociception. Animals given MPF4 (1.0 mmol/kg, i.p.) daily for 8 days in a row, in contrast to morphine (5 mg/kg, i.p.), showed no tolerance to its antinociceptive effect or cross-tolerance with morphine. However, similarly to morphine (11 mg/kg, i.p.), MPF4 (1.0 mmol/kg, i.p.) reduced gastrointestinal transit in mice and its effect was reversed by naloxone (2.5 mg/kg, i.p.). Unlike indomethacin (0.1 mmol/kg, p.o.), MPF4 (1.0 mmol/kg, p.o.) did not induce gastric lesions in mice. The tested compounds did not impair locomotion in the mice as well. Taken together, the results demonstrate that these novel pyrazoline methyl esters evaluated may be promising prototypes of additional mild analgesics, which are therapeutically relevant.